2012
DOI: 10.1021/jp3052856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rare Earth Elements and Alloy Composition on Hydrogenation Properties and Crystal Structures of Hydrides in Mg2–xRExNi4

Abstract: The effect of the rare earth elements and alloy composition on the hydrogenation properties and crystal structures of hydrides in Mg2–x RE x Ni4 (RE = La, Pr, Nd, Sm, and Gd; x = 0.6 and 1.0) was investigated. All Mg2–x RE x Ni4 alloys had a C15b Laves phase before hydrogenation. Mg1.4 RE 0.6Ni4 (RE = Pr, Sm, and Gd) alloys were hydrogenated through one plateau to form Mg1.4 RE 0.6Ni4H∼3.6 while maintaining the C15b structure. Mg1.0 RE 1.0Ni4 (RE = La, Pr, and Nd) alloys were hydrogenated to ∼1.0 H/M proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
6
27
0
Order By: Relevance
“…The detailed structures of the two hydrides, MgPrNi 4 H ³4 and MgPrNi 4 H ³6 , will be reported elsewhere. 14) XRD profiles of Mg 0.8 Pr 1.2 Ni 4 and Mg 0.6 Pr 1.4 Ni 4 after hydrogenation indicate that hydrogeninduced amorphization occurred in these compositions. Aoki et al 15,16) indicated that the ratio of the atomic radii, R A /R B , is a dominant factor for controlling the hydrogeninduced amorphization, where R A and R B are the atomic radii of A and B atoms in C15-type AB 2 …”
Section: Crystal Structuresmentioning
confidence: 90%
“…The detailed structures of the two hydrides, MgPrNi 4 H ³4 and MgPrNi 4 H ³6 , will be reported elsewhere. 14) XRD profiles of Mg 0.8 Pr 1.2 Ni 4 and Mg 0.6 Pr 1.4 Ni 4 after hydrogenation indicate that hydrogeninduced amorphization occurred in these compositions. Aoki et al 15,16) indicated that the ratio of the atomic radii, R A /R B , is a dominant factor for controlling the hydrogeninduced amorphization, where R A and R B are the atomic radii of A and B atoms in C15-type AB 2 …”
Section: Crystal Structuresmentioning
confidence: 90%
“…Basically obtained materials are the mixtures of Laves AB2, Haucke AB5 or/and superlattice (AB2)n(AB5)m phases. Among them the RMgNi4 phases are characterized by good solid gas and electrochemical properties and can be easily prepared by sintering or induction melting methods [6][7][8][9][10][11][12][13][14][15][16][17][18]. Recently, the YMgNi4-xCox [19], LaMgNi4-xCox [20], NdMgNi4-xCox [21], La1-xNdxMgNi4-yCoy [22] and Pr1-xLaxMgNi4-yCoy [23] alloy systems were systematically investigated in our research group.…”
Section: Introductionmentioning
confidence: 99%
“…Highest discharge capacity of the electrodes for these materials can reach 400 mAh/g [3]. Although there are many studies on the hydrogen adsorption properties of the multi phase alloys which containg RMgM4 intermetallics [4], a comprehensive study of single-phase RMgM4 samples is limited to a few dozen works, most of which are devoted to the study of stoichiometric 1:1:4 composition [5][6][7][8][9][10][11][12][13]. In our recent studies we shown the effect of the rare earth and transition metals substitution on the hydrogen sorbtion properties based on the LaMgNi4 compound [14][15].…”
Section: Introductionmentioning
confidence: 99%